Casting technology for high-purity alumina ceramic substrate thick film prepared from sub-nano-scale powder
Through the high-purity alumina ceramic substrate casting slurry formula technology and optimized casting parameters prepared in thick film casting technology, lightweight, high-purity, fine powder thick film flow is solved. The problems of uneven distribution of particles and poor stability of the radial medium have achieved high-quality and high-purity thick film diaphragm preparation.
Patent Information
- Application Number
- CN202411339168.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, problems such as uneven particle distribution in the slurry, poor agglomeration stability, and excessively high or low stacking density are likely to occur during the casting of thick films of lightweight, high and sub-nanometer-level powders.
By providing a high-purity alumina substrate thick film casting technology prepared by sub-nano-grade powder, including high-purity alumina ceramic substrate casting slurry formula technology and thick film casting technology prepared by sub-nano-grade powder , the specific steps include pretreating the alumina powder, formulating slurry, ball milling and filtration, controlling the viscosity and particle size distribution, and optimizing casting parameters to obtain a uniform, high-quality thick film diaphragm.
Achieve uniform dispersion and stability of fine powder (subnano-level) and light powder slurry, ensuring smooth surface, defect-free and uniform thickness of thick film diaphragm, meeting the performance of high-purity alumina ceramic substrate Require.
Smart Images

Figure CN119462085A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic substrate materials and preparation methods, and in particular to a high-purity alumina ceramic substrate tape casting slurry formulation technology prepared from sub-nanometer level powder, a thick film tape casting technology and a preparation method for a high-purity alumina ceramic substrate. Background Art
[0002] Alumina ceramics are widely used in the electronics industry to manufacture integrated circuit substrates, electronic ceramic capacitors, packages, dielectrics and insulating materials. As a substrate material, alumina ceramics are used to manufacture high-frequency circuits and microwave components, which can achieve higher operating frequencies and lower signal losses. The high insulation performance of alumina ceramics effectively prevents leakage and interference of electronic components, and improves the reliability and stability of the circuit; the low dielectric constant and excellent mechanical properties make it possible to make dimensionally stable, high-temperature resistant and corrosion-resistant packaging components, which are used to protect and fix electronic components, and improve their reliability and life; its good thermal conductivity ensures heat dissipation, and the components function better within the working range.
[0003] With the continuous development and intelligent trend of electronic products, the demand for high-performance ceramic materials continues to increase. High-purity alumina ceramics have excellent high-temperature resistance and maintain stable structure and performance in high-temperature environments above 1500°C. High-purity alumina ceramics are a good insulating material that can be used to manufacture insulating layers and high-voltage insulating components for electronic devices. High-purity alumina ceramics have good high-frequency characteristics and mechanical shock resistance, and can be used to prepare large-size, complex-structure components for high-frequency scenarios.
[0004] Taking 99.6% alumina ceramics as an example, the preparation of high-purity alumina ceramics requires raw materials of higher purity to eliminate the influence of impurities. The presence of impurities may cause the performance of ceramic materials to deteriorate, such as electrical properties, mechanical strength, thermal conductivity, chemical stability, etc. The higher the purity of alumina, the higher the sintering temperature. In order to achieve the densification of alumina ceramics at a lower sintering temperature, it is necessary to use finer powders (sub-nanometer powders, or even nano powders) and add a glass phase system to cool down and sinter. Adding a glass phase system to cool down and sinter can easily reduce the purity and mechanical strength of alumina ceramics, and the doping amount of 99.6% alumina ceramics left for the glass phase system is no more than 0.4%, and the adjustable space is very narrow. Fine powder helps to control the microstructure of ceramic materials, obtain a more uniform particle distribution and a finer grain size, and help to improve the density, insulation, better high-frequency dielectric properties, hardness, wear resistance, and processability of ceramics. Therefore, the design of high-purity alumina ceramics often adopts a parallel approach of fine powder and adding a glass phase system.
[0005] Thick film casting is a method for preparing high-performance alumina ceramic diaphragms. It can quickly and efficiently prepare large-area, high-quality, and uniformly thick alumina diaphragms, which is very suitable for industrial production. However, light fine powders aggregate into agglomerates due to electrostatic repulsion or other physical and chemical effects between particles, resulting in reduced stability of the slurry, which is not conducive to the preparation of diaphragms; there may also be problems such as particle blockage and uneven coverage during the scraping or spraying process, resulting in uneven thickness of the thick film, affecting its performance; thick film casting has very high requirements on slurry parameters, especially the state of the powder in the slurry such as solid content, viscosity, powder morphology, particle size, etc. The bulk density of the powder will affect the fluidity and coating performance of the slurry. Too high or too low bulk density may lead to slurry instability or poor coating uniformity.
[0006] Therefore, it is urgent to develop a thick film casting technology for sub-nanometer-level alumina powder to improve the quality of fine powder and lightweight powder thick film casting film.
[0007] In view of this, this application is filed. Summary of the invention
[0008] The purpose of the present invention is to provide a high-purity alumina substrate thick film casting technology prepared from sub-nanometer level powders, including a high-purity alumina ceramic substrate casting slurry formulation technology and a thick film casting technology prepared from sub-nanometer level powders, and to prepare a high-purity alumina ceramic substrate for verification, so as to solve the problems of uneven particle distribution in the slurry, poor agglomeration stability, and too high or too low packing density that are easily encountered in the thick film casting process of lightweight, high-purity, fine powder (sub-nanometer level) powders in the prior art.
[0009] The present invention is achieved through the following technical solutions:
[0010] First, the present invention provides a ceramic slurry formula of fine powder (sub-nanometer level) and lightweight powder, including raw material composition:
[0011] (35-60) parts of solvent, (35-60) parts of aluminum oxide powder, (0.1-0.2) parts of synthetic material, (0.1-2) parts of dispersant and (0-1) parts of defoaming agent.
[0012] The solvent has the functions of providing a dissolving medium, dissolving dispersed powders and additives, adjusting the viscosity of the solution, controlling the subsequent film drying speed, and affecting the coating properties. Preferably, the solvent includes a mixture of at least two of ethanol, methyl ethyl ketone, trichloroethylene, toluene, xylene, methyl tert-butyl ether, ethylene glycol propyl ether, methanol, ethyl acetate, n-butanol, acrylic acid, etc. Exemplarily, the solvent is a mixture of ethanol and methyl ethyl ketone, a mixture of ethanol and toluene, a mixture of ethanol and trichloroethylene, a mixture of toluene and n-butanol, a mixture of acrylic acid and toluene, and a mixture of ethanol, ethyl acetate and toluene. As a preferred embodiment of the present invention, the solvent is a mixture of ethanol, ethyl acetate and toluene, wherein the ratio of ethanol, ethyl acetate and toluene is 1: (0.3-1): (2.6-6). Exemplarily, the solvent is a mixed solvent of ethanol, ethyl acetate and toluene, and the ratio of ethanol, ethyl acetate and toluene is 1: 0.4: 3.24.
[0013] The solvent selected in the embodiment of the present invention has good solubility, can disperse powders, dissolve adhesives, plasticizers, leveling agents, etc.; it is volatile, and during the casting process, the high temperature of the drying oven will volatilize part of the solvent, making the film easier to form; and it has a low boiling point (ethanol is 78.37°C, ethyl acetate is 77°C, and toluene is 110.6°C), which makes it easier to decompose and evaporate during the sintering process.
[0014] Preferably, the alumina powder is a sub-nanometer spherical powder with a particle size satisfying D 50 (100~800)nm, (D 90- D 10 ) / 2D 50 The value is (1.00±0.10). Sub-nano alumina powder is prepared by chemical method, with good dispersion and not easy to agglomerate.
[0015] The composite includes a glass phase + a portion of aluminum oxide, the ratio of the glass phase to the portion of aluminum oxide is 1:n, and n is 2 to 5. The glass phase system is doped with a modified high-purity aluminum oxide ceramic, and the temperature is reduced to sinter. For example, the glass phase system includes CaO-Al2O 3 -SiO 2 、CaO-MgO-SiO 2 MgO-Al 2 O 3 -SiO 2 、CaO-MgO-Al 2 O 3 -SiO 2 and CaO-B 2 O 3 -SiO 2 Preferably, the glass phase system is CaO-MgO-SiO 2System, CaO, MgO, SiO 2 The ratio of MgO / (CaO+MgO+SiO 2 )≤1 / 3, and SiO 2 / CaO is 1.56~2.16;
[0016] The dispersant has the functions of dispersing powder, improving the stability of slurry, improving the processing performance of slurry, and improving the fluidity and uniformity during the casting process. The dispersant is a mixture of one or more of sodium dodecyl sulfate (SDS), sodium octanoate, citric acid, acetic acid, polyphosphate, tert-butylphenyl phosphate (TBP), diethylenediamine, triethanolamine, etc. Preferably, the dispersant is a mixture of dimethylethylenediaminetetraacetate (DTPMP), citric acid, and tert-butylphenyl phosphate (TBP), and the ratio thereof is (15-35): (20-40): (10-20).
[0017] The defoamer has the functions of eliminating surface tension, preventing the formation of bubbles inside the liquid, ensuring the uniformity and stability of the slurry, improving the quality of the slurry coating, and improving the process stability and efficiency during the casting process. The defoamer is a mixture of one or more of fatty alcohol polyoxyethylene ether, silicate, polydimethylsiloxane (PDMS), octanol, decanol, polyether-modified silicone, polyoxypropylene glycerol ether, etc.; preferably, the defoamer is a mixture of polydimethylsilane (PDMS), polyoxypropylene glycerol ether (PGE), and octanol, and the ratio is (35-50): (20-35): (10-20).
[0018] In the second aspect, the present invention provides a thick film tape casting technology of fine powder (sub-nanometer level), lightweight alumina ceramic powder, the prepared slurry is used for thick film slurry tape casting, and the slurry uses sub-nanometer level high-purity alumina, which has the characteristics of lightness. Therefore, the technology includes two parts: thick film slurry preparation and thick film tape casting parameter control.
[0019] Among them, the specific steps of preparing thick film slurry are as follows:
[0020] S1: pre-treat the sub-nanometer alumina powder to be used, with a baking temperature of (120-200)°C and a baking time of (24±5)h to ensure that the alumina powder has no excess moisture, is dry, and does not agglomerate;
[0021] S2: The solvent described in the first aspect, the alumina powder treated in S1, the synthetic material, the dispersant, and the defoaming agent are added in sequence, stirred for 2 hours, and then ball milled at a speed of (800-1200) r / min, and the cycle is maintained every (15±5) min to make the slurry mixed and dispersed uniformly to prepare a uniformly dispersed slurry;
[0022] S3: Adding a binder, a plasticizer and a leveling agent to the slurry in S2, and continuing to mix and stir the mixture, and ball milling the mixture at a speed of (800-1200) r / min, and maintaining a cycle every (15±5) min, to finally obtain a slurry with stable chemical properties and good surface quality;
[0023] S4: Filter the prepared slurry, remove bubbles in vacuum, and control the viscosity to obtain an alumina ceramic slurry that meets the requirements. The slurry is required to meet the following conditions: uniform dispersion, narrow powder particle size distribution range, no bubbles, stable chemical properties, etc.
[0024] Preferably, the ball milling method is a high-speed dispersing sand mill to disperse and control the particle size distribution range of the slurry.
[0025] It should be noted that the raw materials of the glass phase (such as CaO, MgO, SiO 2 ) and part of alumina are ball milled, dried, calcined, ball milled or sand milled to obtain a synthetic material. Specifically, alcohol is used as a medium for mixed ball milling, and after drying, the pre-synthesis is calcined at (1050±100)℃, and the particle size distribution is obtained by ball milling or sand milling to meet (D 90 -D 10 ) / 2D 50 The composite is 1.00±0.10.
[0026] Preferably, the viscosity of the alumina ceramic slurry of the sub-nanometer powder is (8000-20000) cp, and a slurry with a suitable viscosity is obtained so as to flow out a thick film membrane of a certain thickness, more preferably (10000-15000) cp. In order to ensure the stacking density of the membrane, the particle size distribution range of the ceramic slurry is controlled, and the particle size distribution of the alumina ceramic slurry meets D 50 is (80~600)nm, (D 90 -D 10 ) / 2D 50 The value of is (0.4±0.2). Preferably, the slurry particle size distribution is controlled within: D 50 is (80~200)nm, (D 90 -D 10 ) / 2D 50 The value is (0.3±0.1).
[0027] Preferably, the ratios of the adhesive, plasticizer and leveling agent are (5-20) parts, (0-3) parts and (0-2) parts respectively;
[0028] The binder provides adhesion, enhances mechanical properties, adjusts rheology and surface properties, adjusts the surface properties of the final ceramic membrane, ensures the uniform dispersion and effective bonding of the components in the slurry, and directly affects the final quality and performance of the membrane. The binder is a mixture of at least two of polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinyl chloride (PVC), polymethyl methacrylate (PMMA), polyacrylate (PAA), polyacrylamide (PAM), polyurethane, epoxy resin, phenolic resin, methyl cellulose, ethyl cellulose, etc. Preferably, the binder is a mixture of polyvinyl butyral (PVB), phenolic resin, and ethyl cellulose in a ratio of (65-75): (15-20): (5-15).
[0029] The plasticizer increases ductility, improves rheology, enhances flexibility, and adjusts the softness, hardness, and elasticity of the membrane. The plasticizer is at least one of dioctyl phthalate (DOP), diisooctyl phthalate (DIOP), trimethyl phosphate, tributyl phosphate, di-ethylhexyl phthalocyanine alcohol, di-octanoic acid hexyl ester (DOA), dibutyl phthalocyanine alcohol (DBP), etc. Preferably, the plasticizer is dioctyl phthalate (DOP).
[0030] The leveling agent improves surface flatness, eliminates bubbles and defects, and enhances wettability. It improves the quality and appearance of the film by improving the surface characteristics during coating or extrusion. The leveling agent is at least one of isophorone, diacetone alcohol, Solvesso 150, fluorine-modified acrylic acid, phosphate-modified acrylic acid, polydimethylsiloxane, polyether-modified dimethylsiloxane, polymethyl alkylsiloxane, organic modified polysiloxane, etc.; preferably, the leveling agent is polyether-modified dimethylsiloxane.
[0031] Among them, the thick film casting parameter control includes the temperature of each drying channel, the speed of the fan and the casting speed to adjust the degree of dryness during the ceramic film forming process and improve defects such as cracking; the gap between the scraper at the casting head is controlled to control the thickness of the ceramic film and prepare sub-nanometer level alumina thick film sheets.
[0032] In the embodiment of the present invention, the film undergoes heating and cooling stages during the casting process. If the temperature is too fast or uneven, it will cause uneven temperature gradient inside and on the surface of the film, causing thermal stress, deformation, etc., thereby affecting the quality of the film, causing cracking, film failure, etc. Therefore, it is necessary to control the drying tunnel temperature, fan speed and casting speed to ensure uniform heating and cooling, avoid too fast or too slow temperature changes, reduce the stress caused by deformation, and obtain a good quality, defect-free film.
[0033] The drying tunnels include 3 hot air drying tunnels and 7 bottom plate drying tunnels, the temperature of the hot air drying tunnels is (20-40)°C, and the temperature of the bottom plate drying tunnels is (20-60)°C; preferably, the temperature of the hot air drying tunnels is (30±5)°C, and the temperature of the bottom plate drying tunnels is (40±10)°C.
[0034] The fan comprises an air inlet fan, an exhaust fan and a transition bin fan, the rotation speed of the air inlet fan is (500-3000) r / min, the rotation speed of the exhaust fan is (1000-6000) r / min, and the rotation speed of the transition bin fan is (2000-4000) r / min; preferably, the rotation speed of the air inlet fan is (800-2000) r / min, the rotation speed of the exhaust fan is (1000-3000) r / min, and the rotation speed of the transition bin fan is (2000-3000) r / min.
[0035] The casting speed is reflected by the carrier speed, which is (0.5-4) m / min. Preferably, the carrier speed is (2.0±1.0) m / min.
[0036] In the embodiment of the present invention, it is very important to control the gap of the scraper at the casting head, which directly affects the quality and production efficiency of the casting product. The scraper gap directly affects the thickness of the casting product. The appropriate scraper gap affects the flow speed and fluidity, ensures the uniformity and surface finish of the film during the casting process, and improves the production efficiency of the casting.
[0037] The gap between the scraper blades of the casting head is (350-850) μm, preferably, the gap between the scraper blades is (600±100) μm, and a sub-nanometer aluminum oxide thick film with a thickness of (165±5) μm is prepared.
[0038] Finally, the third aspect provides the use of the slurry described in the first aspect and the diaphragm described in the second aspect in the preparation of a high-purity alumina ceramic substrate to prepare a high-purity alumina ceramic substrate that meets specific properties.
[0039] The debonding temperature is (300-500)°C, and the debonding time is (48±12)h;
[0040] The sintering temperature is (1380-1450)°C, and the sintering time is (10±5)h.
[0041] Compared with the prior art, the embodiments of the present invention have the following advantages and beneficial effects:
[0042] 1. To ensure the thick film casting of fine powder (sub-nanometer level) and light powder (alumina powder), this patent provides the corresponding slurry dispersion technology, thick film casting technology and application verification (preparation of high-purity alumina substrate);
[0043] 2. To ensure the preparation of uniform and well-dispersed fine powder (sub-nanometer level) and light powder slurry, control is carried out from two aspects: slurry formulation and process. The slurry viscosity is controlled at (10000-15000) cp and the slurry particle size distribution is controlled at: D 50 is (80~200)nm, (D 90 -D 10 ) / 2D 50 The value is (0.3±0.1).
[0044] 3. In order to obtain a high-purity alumina thick film with a smooth surface, no defects and uniform thickness, the casting process parameters (drying tunnel temperature, fan speed, carrier speed, scraper height) are controlled to prepare a sub-nano alumina ceramic thick film with a thickness of (165±5) μm.
[0045] 4. To verify the reliability of slurry dispersion and thick film casting technology, the embodiment of the present invention prepares a high-purity alumina ceramic substrate (alumina purity ≥ 99.6%) with the following performance conditions: dielectric constant ε (@1MHz, 1.9GHz, 5.1GHz, 10GHz, 15GHz): 9.9±0.2, dielectric loss tanδ (@1MHz, 1.9GHz, 5.1GHz, 10GHz, 15GHz) ≤ 0.0003, bending strength σ ≥ 550MPa, linear expansion coefficient α l (20~950℃):(8.2±0.5)×10 -6 / ℃, and the dielectric constant and dielectric loss both maintain stable changes, which can be used for high-frequency applications and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0047] Figure 1 This is a flow chart of the preparation of sub-nanometer alumina ceramic slurry in an embodiment of the present invention;
[0048] Figure 2 This is a particle size distribution diagram of the sub-nanometer alumina ceramic slurry described in Example 7 of the present invention;
[0049] Figure 3 This is a SEM image of the sub-nanometer aluminum oxide powder single-layer thick film film described in Example 7 of the present invention; wherein Figure 3 a is the front view, Figure 3 b is the reverse side.
[0050] Figure 4 This is a SEM image of a single-layer thick film of sub-nanometer aluminum oxide powder described in Example 7 of the present invention; Figure 4 c is the front view, Figure 4 d is the reverse side. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0052] Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] The embodiment of the present invention provides a high-purity alumina substrate thick film casting technology prepared from sub-nanometer powder, including a high-purity alumina ceramic substrate casting slurry formulation technology and a thick film casting technology prepared from sub-nanometer powder, and prepares a high-purity alumina ceramic substrate for verification, which is specifically implemented according to the following steps:
[0054] (1) Formulation of sub-nano-level alumina ceramic slurry
[0055] (35-60) parts of solvent, (35-60) parts of aluminum oxide powder, (0.1-0.2) parts of synthetic material, (0.1-2) parts of dispersant and (0-1) parts of defoaming agent.
[0056] Specifically, the solvent is a mixed solvent of ethanol, ethyl acetate and toluene, and the ratio of ethanol, ethyl acetate and toluene is 1:0.4:3.24; the alumina powder is a sub-nanometer spherical powder, and the particle size meets D 50 (100~800)nm, (D 90- D 10 ) / 2D 50 The value is (1.00±0.10); the composite includes glass phase + partial aluminum oxide, the ratio of glass phase: partial aluminum oxide is 1:n, and n is 2 to 5. The glass phase system is CaO-MgO-SiO 2 System, CaO, MgO, SiO 2 The ratio of MgO / (CaO+MgO+SiO 2 )≤1 / 3, and SiO 2 / CaO is 1.56-2.16; the dispersant is a mixture of dimethylethylenediaminetetraacetate (DTPMP), citric acid, and tert-butylphenylphosphonic acid (TBP), and the ratio thereof is (15-35): (20-40): (10-20). The defoaming agent is a mixture of polydimethylsilane (PDMS), polyoxypropylene glycerol ether (PGE), and octanol, and the ratio thereof is (35-50): (20-35): (10-20).
[0057] (2) A thick film casting technology for fine powder (sub-nanometer level) and lightweight alumina ceramic powder
[0058] This technology includes two parts: thick film slurry preparation and thick film casting parameter control.
[0059] Among them, the thick film slurry is prepared to obtain sub-nanometer-level alumina ceramic slurry that meets the requirements. The specific requirements of the slurry are: viscosity controlled at (8000-20000) cp, uniform dispersion, narrow powder particle size distribution range, no bubbles, stable chemical properties, etc.
[0060] Specifically, the sub-nanometer alumina powder used is pretreated, the baking temperature is (120-200)°C, and the baking time is (24±5)h; the solvent, alumina powder, a synthetic material, a dispersant, and a defoaming agent are added in sequence and stirred for 2h, and then ball milled at a speed of (800-1200)r / min, and the slurry is mixed and dispersed evenly; (5-20) parts of a binder, (0-3) parts of a plasticizer, and (0-2) parts of a leveling agent are added, and the mixing and stirring are continued, and the ball milling is carried out at a speed of (800-1200)r / min, and the slurry is circulated once every (15±5)min; filtering and vacuum degassing are performed to control the viscosity, and the alumina ceramic slurry that meets the requirements is obtained, and the viscosity requirement is (10000-15000)cp, and the particle size distribution is controlled within: D 50 is (80~200)nm, (D 90 -D 10 ) / 2D 50 The value is (0.3±0.1).
[0061] The adhesive is a mixture of polyvinyl butyral (PVB), phenolic resin and ethyl cellulose in a ratio of (65-75): (15-20): (5-15), the plasticizer is dioctyl phthalate (DOP), and the leveling agent is polyether modified dimethyl siloxane.
[0062] Among them, the thick film casting parameters controlled include the temperature of each drying channel, the rotation speed of the fan, the casting speed, and the gap between the scraper and the casting head, so as to obtain a sub-nanometer-level aluminum oxide thick film sheet with good surface quality and no defects that meets the thickness requirements ((165±5)μm).
[0063] Specifically, the drying tunnel includes 3 hot air drying tunnels and 7 bottom plate drying tunnels. The temperature of the hot air drying tunnel is (30±5)°C, and the temperature of the bottom plate drying tunnel is (40±10)°C. The speed of the fan in the air inlet area is (800~2000)r / min, the speed of the fan in the exhaust area is (1000~3000)r / min, and the speed of the fan in the transition bin is (2000~3000)r / min. The carrier speed is (2.0±1.0)m / min. The scraper gap is (600±100)μm, and a sub-nanometer-level aluminum oxide thick film with a thickness of (165±5)μm is prepared.
[0064] (3) High purity alumina ceramic substrate.
[0065] Specifically, the above-mentioned sub-nano alumina ceramic thick film diaphragm is used in the preparation of high-purity alumina ceramic substrates to prepare high-purity alumina ceramic substrates that meet specific performance requirements. More specifically, the above-mentioned sub-nano alumina ceramic thick film diaphragm is prepared into a raw ceramic body of corresponding specifications, which is then sintered into ceramics through debonding.
[0066] Among them, the debonding temperature is (300-500)°C, and the debonding time is (48±12)h; the sintering temperature is (1380-1450)°C, and the sintering time is (10±5)h.
[0067] Example 1
[0068] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0069] First, 35.8 parts of alumina powder, 60 parts of solvent, 0.1 parts of synthetic material, 0.1 parts of dispersant, 0 parts of defoaming agent, 4 parts of adhesive, 0 parts of plasticizer, and 0 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0070] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0071] Drying tunnel temperature: 25°C (hot air 1), 25°C (hot air 2), 25°C (hot air 3), 30°C (bottom plate 1), 32°C (bottom plate 2), 36°C (bottom plate 3), 40°C (bottom plate 4), 42°C (bottom plate 5), 42°C (bottom plate 6), 40°C (bottom plate 7);
[0072] Fan speed: 1500r / min (inlet area), 2500r / min (exhaust area), 2800r / min (transition area);
[0073] The casting speed is reflected by the carrier speed, which is 1.5m / min;
[0074] The casting head blade gap was 550 μm.
[0075] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 350°C and keeping warm for 48 hours, and sintering at 1420°C and keeping warm for 10 hours.
[0076] Example 2
[0077] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0078] First, 45 parts of alumina powder, 45 parts of solvent, 0.15 parts of synthetic material, 1.85 parts of dispersant, 0 parts of defoaming agent, 7 parts of adhesive, 1 part of plasticizer, and 0 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0079] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0080] Drying tunnel temperature: 35°C (hot air 1), 35°C (hot air 2), 35°C (hot air 3), 35°C (bottom plate 1), 37°C (bottom plate 2), 39°C (bottom plate 3), 43°C (bottom plate 4), 45°C (bottom plate 5), 45°C (bottom plate 6), 43°C (bottom plate 7);
[0081] Fan speed: 2000r / min (inlet area), 3000r / min (exhaust area), 3500r / min (transition area);
[0082] The casting speed is reflected by the carrier speed, which is 3m / min;
[0083] The casting head blade gap was 600 μm.
[0084] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 350°C and keeping warm for 48 hours, and sintering at 1420°C and keeping warm for 10 hours.
[0085] Example 3
[0086] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0087] First, 38 parts of alumina powder, 45.9 parts of solvent, 0.1 parts of synthetic material, 2 parts of dispersant, 0.5 parts of defoaming agent, 10 parts of adhesive, 2 parts of plasticizer, and 1.5 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0088] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0089] Drying tunnel temperature: 35°C (hot air 1), 35°C (hot air 2), 35°C (hot air 3), 35°C (bottom plate 1), 37°C (bottom plate 2), 39°C (bottom plate 3), 43°C (bottom plate 4), 45°C (bottom plate 5), 45°C (bottom plate 6), 43°C (bottom plate 7);
[0090] Fan speed: 2000r / min (inlet area), 3000r / min (exhaust area), 3500r / min (transition area);
[0091] The casting speed is reflected by the carrier speed, which is 3m / min;
[0092] The casting head blade gap was 600 μm.
[0093] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 350°C and keeping it warm for 36 hours, and sintering at 1420°C and keeping it warm for 12 hours.
[0094] Example 4
[0095] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0096] First, 35.4 parts of alumina powder, 55 parts of solvent, 0.1 parts of synthetic material, 1 part of dispersant, 0 parts of defoaming agent, 5.5 parts of adhesive, 3 parts of plasticizer, and 0 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0097] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0098] Drying tunnel temperature: 25°C (hot air 1), 25°C (hot air 2), 25°C (hot air 3), 30°C (bottom plate 1), 32°C (bottom plate 2), 36°C (bottom plate 3), 40°C (bottom plate 4), 42°C (bottom plate 5), 42°C (bottom plate 6), 40°C (bottom plate 7);
[0099] Fan speed: 1500r / min (inlet area), 2500r / min (exhaust area), 2800r / min (transition area);
[0100] The casting speed is reflected by the carrier speed, which is 1.5m / min;
[0101] The casting head blade gap was 550 μm.
[0102] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 350°C and keeping warm for 48 hours, and sintering at 1420°C and keeping warm for 10 hours.
[0103] Example 5
[0104] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0105] First, 35.4 parts of alumina powder, 55 parts of solvent, 0.1 parts of synthetic material, 1 part of dispersant, 0 parts of defoaming agent, 5.5 parts of adhesive, 3 parts of plasticizer, and 0 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0106] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0107] Drying tunnel temperature: 25°C (hot air 1), 25°C (hot air 2), 25°C (hot air 3), 30°C (bottom plate 1), 32°C (bottom plate 2), 36°C (bottom plate 3), 40°C (bottom plate 4), 42°C (bottom plate 5), 42°C (bottom plate 6), 40°C (bottom plate 7);
[0108] Fan speed: 1500r / min (inlet area), 2500r / min (exhaust area), 2800r / min (transition area);
[0109] The casting speed is reflected by the carrier speed, which is 1.5m / min;
[0110] The casting head blade gap was 550 μm.
[0111] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 400°C and keeping it warm for 44 hours, and sintering at 1450°C and keeping it warm for 5 hours.
[0112] Example 6
[0113] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0114] First, 38 parts of alumina powder, 41.2 parts of solvent, 0.1 parts of synthetic material, 1.2 parts of dispersant, 0.5 parts of defoaming agent, 15.5 parts of adhesive, 2 parts of plasticizer and 1.5 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0115] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0116] Drying tunnel temperature: 25°C (hot air 1), 25°C (hot air 2), 25°C (hot air 3), 30°C (bottom plate 1), 32°C (bottom plate 2), 36°C (bottom plate 3), 40°C (bottom plate 4), 42°C (bottom plate 5), 42°C (bottom plate 6), 40°C (bottom plate 7);
[0117] Fan speed: 1500r / min (inlet area), 2500r / min (exhaust area), 2800r / min (transition area);
[0118] The casting speed is reflected by the carrier speed, which is 1.5m / min;
[0119] The casting head blade gap was 550 μm.
[0120] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 350°C and keeping warm for 48 hours, and sintering at 1420°C and keeping warm for 10 hours.
[0121] Example 7
[0122] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0123] First, 38 parts of alumina powder, 41.2 parts of solvent, 0.1 parts of synthetic material, 1.2 parts of dispersant, 0.5 parts of defoaming agent, 15.5 parts of adhesive, 2 parts of plasticizer and 1.5 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0124] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0125] Drying tunnel temperature: 25°C (hot air 1), 25°C (hot air 2), 25°C (hot air 3), 30°C (bottom plate 1), 32°C (bottom plate 2), 36°C (bottom plate 3), 40°C (bottom plate 4), 42°C (bottom plate 5), 42°C (bottom plate 6), 40°C (bottom plate 7);
[0126] Fan speed: 1500r / min (inlet area), 2500r / min (exhaust area), 2800r / min (transition area);
[0127] The casting speed is reflected by the carrier speed, which is 1.5m / min;
[0128] The casting head blade gap was 550 μm.
[0129] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 400°C and keeping it warm for 44 hours, and sintering at 1450°C and keeping it warm for 5 hours.
[0130] Example 8
[0131] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0132] First, 38 parts of alumina powder, 41.2 parts of solvent, 0.1 parts of synthetic material, 1.2 parts of dispersant, 0.5 parts of defoaming agent, 15.5 parts of adhesive, 2 parts of plasticizer and 1.5 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0133] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0134] Drying tunnel temperature: 25°C (hot air 1), 25°C (hot air 2), 25°C (hot air 3), 30°C (bottom plate 1), 32°C (bottom plate 2), 36°C (bottom plate 3), 40°C (bottom plate 4), 42°C (bottom plate 5), 42°C (bottom plate 6), 40°C (bottom plate 7);
[0135] Fan speed: 1500r / min (inlet area), 2500r / min (exhaust area), 2800r / min (transition area);
[0136] The casting speed is reflected by the carrier speed, which is 1.5m / min;
[0137] The casting head blade gap was 550 μm.
[0138] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 350°C and keeping it warm for 36 hours, and sintering at 1420°C and keeping it warm for 12 hours.
[0139] Example 9
[0140] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0141] First, 42 parts of alumina powder, 49.9 parts of solvent, 0.1 parts of synthetic material, 1 part of dispersant, 0 parts of defoaming agent, 6 parts of adhesive, 1 part of plasticizer, and 0 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0142] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0143] Drying tunnel temperature: 25°C (hot air 1), 25°C (hot air 2), 25°C (hot air 3), 30°C (bottom plate 1), 32°C (bottom plate 2), 36°C (bottom plate 3), 40°C (bottom plate 4), 42°C (bottom plate 5), 42°C (bottom plate 6), 40°C (bottom plate 7);
[0144] Fan speed: 2000r / min (inlet area), 3000r / min (exhaust area), 3500r / min (transition area);
[0145] The casting speed is reflected by the carrier speed, which is 2m / min;
[0146] The casting head blade gap was 580 μm.
[0147] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 350°C and keeping warm for 48 hours, and sintering at 1420°C and keeping warm for 10 hours.
[0148] Example 10
[0149] This embodiment provides a high-purity aluminum oxide substrate thick film casting technology prepared from sub-nanometer powder, including the following contents:
[0150] First, 42 parts of alumina powder, 49.9 parts of solvent, 0.1 parts of synthetic material, 1 part of dispersant, 0 parts of defoaming agent, 6 parts of adhesive, 1 part of plasticizer, and 0 parts of leveling agent were weighed and dispersed at high speed to obtain a sub-nanometer-level alumina ceramic slurry that was mixed and dispersed evenly and met the requirements and could be used for thick film casting.
[0151] Secondly, the casting parameters such as drying tunnel temperature, fan speed, casting speed, and scraper gap are controlled to obtain a sub-nanometer aluminum oxide thick film with a film thickness of (165±5)μm. The casting parameters meet the following requirements:
[0152] Drying tunnel temperature: 25°C (hot air 1), 25°C (hot air 2), 25°C (hot air 3), 30°C (bottom plate 1), 32°C (bottom plate 2), 36°C (bottom plate 3), 40°C (bottom plate 4), 42°C (bottom plate 5), 42°C (bottom plate 6), 40°C (bottom plate 7);
[0153] Fan speed: 2000r / min (inlet area), 3000r / min (exhaust area), 3500r / min (transition area);
[0154] The casting speed is reflected by the carrier speed, which is 2m / min;
[0155] The casting head blade gap was 580 μm.
[0156] Finally, the various properties of the prepared high-purity alumina ceramics were verified by debonding at 350°C and keeping it warm for 36 hours, and sintering at 1420°C and keeping it warm for 12 hours.
[0157] Among them, the raw material ratios of the sub-nanometer alumina ceramic slurry for thick film casting of Examples 1-10 are shown in Table 1; the casting parameters of the sub-nanometer alumina ceramic slurry for thick film casting are shown in Table 2; and the debonding sintering scheme used for high-purity alumina ceramics is shown in Table 3.
[0158] The alumina ceramics prepared in each example were subjected to performance tests such as dielectric constant, dielectric loss, flexural strength, and thermal expansion coefficient at different frequencies, including dielectric properties at test frequency points of 1 MHz, 1.9 GHz, 5.1 GHz, 10 GHz, and 15 GHz. The test results are shown in Table 4 below.
[0159] Table 1 Ratio of raw materials in sub-nanometer alumina ceramic slurry for thick film casting
[0160]
[0161] Table 2 Thick film casting parameters of sub-nanometer alumina ceramics
[0162]
[0163] Table 3 Debonding sintering parameters of high purity alumina ceramics
[0164]
[0165]
[0166] Table 4 Performance test results of alumina ceramics prepared in each example
[0167]
[0168]
[0169] It should be noted that the scheme parameters of Example 1 correspond to A1+B1+C1, the scheme parameters of Example 2 correspond to A2+B2+C1, the scheme parameters of Example 3 correspond to A3+B2+C3, the scheme parameters of Example 4 correspond to A4+B1+C1, the scheme parameters of Example 5 correspond to A4+B1+C2, the scheme parameters of Example 6 correspond to A5+B1+C1, the scheme parameters of Example 7 correspond to A5+B1+C2, the scheme parameters of Example 8 correspond to A5+B1+C3, the scheme parameters of Example 9 correspond to A6+B3+C1, and the scheme parameters of Example 10 correspond to A6+B3+C3.
[0170] The sub-nanometer aluminum oxide single-layer thick film of Example 7 was subjected to SEM analysis. Figure 3 and 4 As shown by Figure 3 and Figure 4 It is found that there is no difference between the front and back sides of the sub-nanometer aluminum oxide single-layer thick film film at a low magnification of 2000 times or a high magnification of 60000 times, indicating that the thick film film prepared by the thick film casting preparation method has uniform composition, no stratification, no local appearance difference, etc., and is a qualified, high-quality thick film film. The particle size distribution of the ceramic slurry of Example 7 is shown in FIG. Figure 2 As shown in Table 4, the ceramic material of the embodiment of the present invention meets the following properties: dielectric constant ε (@1MHz, 1.9GHz, 5.1GHz, 10GHz, 15GHz): 9.9±0.2, dielectric loss tanδ (@1MHz, 1.9GHz, 5.1GHz, 10GHz, 15GHz) ≤ 0.0003, bending strength ≥ 550MPa, linear expansion coefficient α l (20~950℃):(8.2±0.5)×10 -6 / ℃, and the dielectric constant and dielectric loss both keep changing steadily.
[0171] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A sub-nanometer alumina ceramic slurry that can be used for thick film casting, characterized in that: Made from the following ingredients: 35-60 parts of solvent, 35-60 parts of alumina powder, 0.1-0.2 parts of synthetic material and 0.1-2 parts of dispersant.
2. The sub-nanometer alumina ceramic slurry for thick film casting according to claim 1, characterized in that: The solvent includes a mixture of at least two of ethanol, methyl ethyl ketone, trichloroethylene, toluene, xylene, methyl tert-butyl ether, ethylene glycol propyl ether, methanol, ethyl acetate, n-butanol, acrylic acid, and the like.
3. The sub-nanometer alumina ceramic slurry for thick film casting according to claim 1, characterized in that: The alumina powder is a sub-nanometer spherical powder, and the particle size satisfies D 50 (100~800)nm, (D 90 -D 10 ) / 2D 50 The value is (1.00±0.10).
4. The sub-nanometer alumina ceramic slurry for thick film casting according to claim 1, characterized in that: The composite comprises a glass phase system and aluminum oxide, wherein the ratio of the glass phase to the aluminum oxide is 1:n, and n is 2-5.
5. The sub-nanometer alumina ceramic slurry for thick film casting according to claim 4, characterized in that: The glass phase system includes at least one of the CaO-Al2O3-SiO2, CaO-MgO-SiO2, MgO-Al2O3-SiO2, CaO-MgO-Al2O3-SiO2 and CaO-B2O3-SiO2 systems.
6. A method for preparing a sub-nanometer alumina ceramic slurry for thick film casting as claimed in claims 1 to 5, characterized in that: The following steps are involved: S1: pretreating alumina powder; S2: mixing and ball-milling the solvent, the alumina powder of S1, the synthetic material, the dispersant, and the defoamer to obtain a mixed slurry; S3: adding a binder, a plasticizer and a leveling agent to the mixed slurry in S2 and continuing ball milling; S4: The slurry in S3 is filtered and vacuum-defoamed to obtain a sub-nanometer-level alumina ceramic slurry that meets the requirements.
7. The method for preparing a sub-nanometer alumina ceramic slurry for thick film casting according to claim 6, characterized in that: The viscosity of the alumina ceramic slurry is 8000-20000cp, and the particle size distribution of the alumina ceramic slurry satisfies D 50 is (80~600)nm, (D 90 -D 10 ) / 2D 50 The value is (0.4±0.2).
8. A sub-nanometer alumina ceramic slurry thick film tape casting technology, characterized in that: The slurry is the alumina ceramic slurry of claim 7, and the thick film casting parameters include the temperature of each drying channel, the rotation speed of the fan, the casting speed and the scraper gap of the casting head.
9. The sub-nanometer level alumina ceramic slurry thick film tape casting technology according to claim 8, characterized in that: The drying tunnels include 3 hot air drying tunnels and 7 bottom plate drying tunnels, the temperature of the hot air drying tunnels is 20-40°C, and the temperature of the bottom plate drying tunnels is 20-60°C; The fan includes an air inlet fan, an exhaust fan and a transition chamber fan. The speed of the air inlet fan is 500-3000r / min, the speed of the exhaust fan is 1000-6000r / min, and the speed of the transition chamber fan is 2000-4000r / min. The casting speed is reflected by the carrier speed, and the carrier speed is 0.5-4 m / min; The gap between the scraper and the casting head is 350-850 μm; The thickness of the sub-nanometer aluminum oxide thick film is 165±5 μm.
10. A method for preparing a high-purity alumina ceramic substrate, characterized in that: The method comprises sequentially debonding and sintering the sub-nanometer aluminum oxide thick film sheet as claimed in claim 9, and then obtaining a ceramic material; The debonding temperature is 300-500°C, and the debonding time is 48±12h; The sintering temperature is 1380-1450° C., and the sintering time is 10±5 h.
Citation Information
Patent Citations
Method for preparing aluminium oxide ceramics green ceramic chip by tape casting
CN101791818A
Method for preparing dense, beta-alumina ceramic bodies by liquid phase sintering
US4138455A
Alumina ceramic and preparation method therefor
WO2021248813A1